Sediment Scouring of the Riverbed Downstream of a Specified Weir Pond - Christine, Maria; Tallar, Robby Yussac (Jurnal Teknik Sipil, 2024)
In planning a water structure such as a weir, it is necessary to first study the problem of local scouring that occurs downstream of the structure. Local scouring problems occur as a result of water velocity and turbulence exceeding the resistance of the channel or river bed material. In this study, a square-shaped channel with a certain size and base slope was used to find the depth of local scouring along with the dry volume of sediment carried. Through 6 experiments by averaging the discharge on the 2 discharge gauges used, the deepest local scour that occurred was 3.8 cm; 4 cm; 4.3 cm; 4.5 cm, 4.8 cm; 5.1 cm and the dry volume of sediment carried was 8305 cm3; 12915 cm3; 18505.71 cm3; 23331.43 cm3; 28760 cm3, 29960.71 cm3. In this study, it can be concluded that Lacey's formula is the closest to laboratory results after reaching equilibrium. The amount of sediment volume carried, is strongly influenced by the diameter of sediment grains, flow discharge, flow velocity and channel slope. The greater the flowing discharge, at a certain time will produce constant scouring. This is because a balance has been reached. The deeper the local scour that occurs, it can be concluded that the more sediment volume is carried downstream of the weir.